Asalib At-Tarbiyah Al-Mustanbathah Min As-Surah Al-Ghosyiyah - Jurais Mahali; Abdul Hayyie Al-Kattani (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
The holly quran is the constitution of the Islmamic nation, the quran descent from the preserved tablet to the sky of the world, then the hostel with Gabriel Alaihi salam for the sake of the creature and the most honorable people of the prophet Muhammad shalallahu ‘alaihi wasalam it is the first source of Islamic law legislation. And Islamic education activities need pedagogy methods from the Quran and Sunnah. These methods are very important because the divine methods were revealed from Allah, who is the Creator of mankind, the knower of what He created. Today, many educators did not use the Islamic education method, not knowing it, He raised a generation without the Islamic education curriculum and Islamic education methods, from which a generation is born that does not know God’s right to it. For this reason, the author has demonstrated these methods of divine education from Surah Al-Ghasyah.